Causal Relationship Model of Food Security Management - Tumpracha, Kruemas; Thiengkamol, Nongnapas; Thiengkamol, Chatchai (Richtmann Publishing, 2012)
The populations were 18,463 upper secondary school students from school under Secondary Service Area Office 24 (Kalasin), Northeastern region of Thailand in academic year of 2012. The Multi-stage random sampling technique was employed to collect the sample for 371 upper secondary school students. The research instrument was the questionnaire and it was used for data collecting. LISREL wFas used for model verification. The objective of this research was to develop causal relationship model of food security management for upper secondary school student of Kalasin Province. Considering on structural model confirmatory factors of Environmental Education (EE) and Food Security Management Characteristics (FC) were able to explain the variation of endogenous factors of Inspiration of Public Consciousness with Food Security Management for Environmental Conservation (FP) to caused Food Security Behaviors (FB) with 54.00 percents. As a result, the equation 1, it can be written as following. FB = 0.57*FP + 0.49*EE - 0.33*FC …………………………(1) R2 = 0.54 Moreover, confirmatory factors of Environmental Education (EE) and Food Security Management Characteristics (FC) were able to explain the variation of confirmatory factors of Inspiration of Public Consciousness with Food Security Management for Environmental Conservation (FP) with 58.00 percents. Therefore, the equation can be written as following equation 2. FP = 0.34*EE + 0.52*FC …………………………..…………(2) R2 = 0.58